2005
DOI: 10.5194/nhess-5-101-2005
|View full text |Cite
|
Sign up to set email alerts
|

Seismically active area monitoring by robust TIR satellite techniques: a sensitivity analysis on low magnitude earthquakes in Greece and Turkey

Abstract: Part of Special Issue "Precursory phenomena, seismic hazard evaluation and seismo-tectonic electromagnetic effects" Abstract. Space-time TIR anomalies, observed from months to weeks before earthquake occurrence, have been suggested by several authors as pre-seismic signals. Up to now, such a claimed connection of TIR emission with seismic activity has been considered with some caution by scientific community mainly for the insufficiency of the validation data-sets and the scarce importance attached by those au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 9 publications
(9 reference statements)
4
25
1
2
Order By: Relevance
“…Corrado et al, 2005) is confirmed, in fact TIR anomalies persistent in the space-time domain have been observed in Italy from few days to few weeks before seismic events of medium-low magnitude (Calabria,8 An original approach to identify and exclude TIR anomalies purely due to the effect (already described in Aliano et al, 2008a) of cloud cover and spatial distribution was proposed. Nevertheless the presence of clouds continue to limit the possibility to well investigate space-time persistence of TIR anomalies.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Corrado et al, 2005) is confirmed, in fact TIR anomalies persistent in the space-time domain have been observed in Italy from few days to few weeks before seismic events of medium-low magnitude (Calabria,8 An original approach to identify and exclude TIR anomalies purely due to the effect (already described in Aliano et al, 2008a) of cloud cover and spatial distribution was proposed. Nevertheless the presence of clouds continue to limit the possibility to well investigate space-time persistence of TIR anomalies.…”
Section: Discussionmentioning
confidence: 78%
“…RST was applied for the first time to seismically active areas monitoring, in the case of the disastrous 1980 Irpinia-Basilicata earthquake (Di Bello et al, 2004;Tramutoli et al, 2001b), then it was successfully tested in several cases: Athens, 7 September 1999 ; Izmit, 17 August 1999 ; Gujarat, 26 January 2001 (Genzano et al, 2007), Boumerdes/Thenia, 21 May 2003(Aliano et al, 2007; Hector Mine, 16 October 1999(Aliano et al, 2008a, Umbria-Marche, October 1997 (Aliano et al, 2008b), Mestia Tianeti (Georgia), 23 October 1992 , and various low magnitude events occurred in Greece and Turkey, May and June 1995-1996(Corrado et al, 2005.…”
Section: A Robust Estimator Of Thermal Anomaliesmentioning
confidence: 99%
See 1 more Smart Citation
“…Tramutoli et al, 2001bTramutoli et al, , 2005Tramutoli et al, , 2009Di Bello et al, 2004;Corrado et al, 2005;Genzano et al, 2007Aliano et al, 2007Aliano et al, , 2008a.…”
Section: Introductionunclassified
“…After its first application to the 1980 Irpinia-Basilicata's earthquake (Di Bello et al, 2004;Tramutoli et al, 2001b) RST has been applied to seismically active area monitoring for several other earthquake events: Athens, 7 September 1999 ; Izmit, 17 August 1999 (Tramutoli et al, 2005); Gujarat, 26 January 2001 (Genzano et al, 2007), Boumerdes/Thenia, 21 May 2003(Aliano et al, 2007; Hector Mine, 16 October 1999 (Aliano et al, 2008a), UmbriaMarche, October 1997 (Aliano et al, 2008b), Mestia Tianeti (Georgia) 23 October 1992 ) and various seismic events occurred in Greece and Turkey, in May and June 1995-1996(Corrado et al, 2005.…”
Section: A Robust Estimator Of Thermal Anomaliesmentioning
confidence: 99%